Uji Kualitas Batubara terhadap Kedalaman Lapisan Daerah Penambangan Pulau Bunyu dengan Metode Proksimat pada Lokasi 4 Pit - Anugerah, Quintiza; Natalisanto, Adrianus Inu; PSP, Devina Rayzy (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2022)
The purpose of this research was motivated by the level of coal quality at each depth of the layer. Each coal company needs to do a quality testing when conducting exploring. In addition to measuring the amount of potential coal reserves, it also measures the quality level of the coal. Whether if carried out exploration or excavation can provide benefits, therefore in this research the author will conduct research on the effect of the depth level of the layer of coal using parameters such as calorific value, total sulfur, fixed carbon, volatile matter, ash, and moisture. As for the place of this research conducted at PT. lamindo inter multikon mining area of Bunyu Island, Bulungan Regency, North Kalimantan Province. From the results of this research it was found that the highest caloric value was the location of PIT 4.